The Effect of Student Teams Achievement Divisions (STAD) on the Learning Outcomes of Grade VIII Students in Indonesian Language at MTs Negeri 2 Kepahiang - Reza adin tya, Nendi; Akbar Jono, Ali; Randi, Randi (Yayasan Darussalam Bengkulu, 2024)
Cooperative learning models have been widely recognized as effective strategies to enhance student achievement, yet their application in Indonesian language instruction at the junior secondary level remains limited. This study aimed to examine the effect of the Student Teams Achievement Division (STAD) cooperative learning model on the learning outcomes of eighth-grade students at MTs Negeri 2 Kepahiang. Employing a quasi-experimental design with a non-equivalent control group, the study involved two classes, with one serving as the experimental group taught using STAD (n = 30) and the other as the control group taught using conventional methods (n = 26). Data were collected through pretests and posttests consisting of 15 multiple-choice items aligned with the curriculum, validated through Pearson’s Product-Moment correlation, and tested for reliability using Cronbach’s Alpha. Statistical analysis using IBM SPSS version 25 included normality and homogeneity tests, paired-sample t-tests, independent-sample t-tests, and N-Gain analysis at a significance level of p < 0.05. The results showed that the experimental group achieved a significantly higher posttest mean score (M = 12.80) compared to the control group (M = 7.34), with the independent-sample t-test confirming a significant difference (p = 0.000). These findings indicate that the STAD model effectively improves student achievement by fostering peer collaboration, active engagement, and collective responsibility for learning outcomes. The novelty of this research lies in its application of STAD in Indonesian language learning at the junior secondary level, providing new insights into cooperative learning beyond science and mathematics, where it has been predominantly studied. The implications suggest that educators and policymakers should integrate cooperative learning models such as STAD into instructional practices to enhance academic performance and social competencies essential for 21st-century learning.